Exportações de melão do estado do Rio Grande do Norte no período de 2000 a 2017: uma análise descritiva - Lopes, Rhuan Carlos da Silva (Universidade Federal Rural do Semi-Árido, 2018)
The melon, vegetable popularly known as a fruit, is part of the list of agricultural commodities exported by Brazil, being in 2017, the second most exported fruit in the country. The state of Rio Grande do Norte, in turn, is one of the largest producers and exporters of national melon. In addition, the melon is of paramount importance to the state's economy and its trade balance. The objective of this study was to analyze the variations of melon exports from the state of Rio Grande do Norte in the period from 2000 to 2017. The data were obtained from the MDIC and IPEA sites and were analyzed descriptively from frames, tables and graphs. It was detailed the participation of each block of importing countries, noting the greater participation of the countries that make up the European Union. In addition, it was observed that exports, in general, tend to follow the variations of the exchange rate, but are not totally dependent.
Monografia
Keywords: Exportações; Países; Melão; Rio Grande do Norte; Variações; Taxa de câmbio; Exports; Country; Melon; Rio Grande do Norte; Variations; Exchange rate; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO